The Arabidopsis chromatin regulator MOM1 is a negative component of the defense priming induced by AZA, BABA and PIP - Miranda de la Torre, Julián O.; Peppino Margutti, Micaela Y.; Lescano López, Ignacio; Cambiagno, Damián Alejandro; Alvarez, María E.; Cecchini, Nicolás M. (Frontiers in Plant Science, 2023)
In plants, the establishment of broad and long-lasting immunity is based on programs that control systemic resistance and immunological memory or "priming". Despite not showing activated defenses, a primed plant induces a more efficient response to recurrent infections. Priming might involve chromatin modifications that allow a faster/stronger activation of defense genes. The Arabidopsis chromatin regulator "Morpheus Molecule 1" (MOM1) has been recently suggested as a priming factor affecting the expression of immune receptor genes. Here, we show that mom1 mutants exacerbate the root growth inhibition response triggered by the key defense priming inducers azelaic acid (AZA), β-aminobutyric acid (BABA) and pipecolic acid (PIP). Conversely, mom1 mutants complemented with a minimal version of MOM1 (miniMOM1 plants) are insensitive. Moreover, miniMOM1 is unable to induce systemic resistance against Pseudomonas in response to these inducers. Importantly, AZA, BABA and PIP treatments reduce the MOM1 expression, but not miniMOM1 transcript levels, in systemic tissues. Consistently, several MOM1-regulated immune receptor genes are upregulated during the activation of systemic resistance in WT plants, while this effect is not observed in miniMOM1. Taken together, our results position MOM1 as a chromatin factor that negatively regulates the defense priming induced by AZA, BABA and PIP.